2001
DOI: 10.1063/1.1368397
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and relaxation of particulate charge in fluorocarbon plasmas

Abstract: Analysis of cathode geometry to minimize cathode erosion in direct current microplasma jet J. Appl. Phys. 112, 123302 (2012) Charging effect simulation model used in simulations of plasma etching of silicon J. Appl. Phys. 112, 084308 (2012) Extraction of negative ions from pulsed electronegative capacitively coupled plasmas J. Appl. Phys. 112, 033303 (2012) High electronegativity multi-dipolar electron cyclotron resonance plasma source for etching by negative ions J. Appl. Phys. 111, 083303 (2012) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…10,11 Furthermore, it has recently been demonstrated that in the bulk of C 4 F 8 ϩAr inductively coupled and surface wave sustained plasmas positive fluorocarbon ions can significantly affect the macroparticle charging and charge relaxation processes. 12 In this article, we consider the effect of negative ions on particulate charging and trapping in the near-electrode region of fluorocarbon plasmas. We assume that the charge proportion on negatively charged dusts is low, and the particulates do not affect the structure of the sheath/presheath region.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Furthermore, it has recently been demonstrated that in the bulk of C 4 F 8 ϩAr inductively coupled and surface wave sustained plasmas positive fluorocarbon ions can significantly affect the macroparticle charging and charge relaxation processes. 12 In this article, we consider the effect of negative ions on particulate charging and trapping in the near-electrode region of fluorocarbon plasmas. We assume that the charge proportion on negatively charged dusts is low, and the particulates do not affect the structure of the sheath/presheath region.…”
Section: Introductionmentioning
confidence: 99%
“…Five thousand particles are statistically sufficient for this purpose, since a larger number had no significant effect on the results. The time step is chosen in such a way that it is greater than the characteristic charging time (Ostrikov et al 2001) and less than the time scale for fluctuations . Hence, the time-average properties of the local sheath field can be used during the calculation of particle trajectory after it departs from its equilibrium position.…”
Section: Analysis Of Particle Deposition On Substratementioning
confidence: 99%
“…The presence of additional negative ions can be considered as another plasma component which are heavier than that of electrons and such plasma exhibits quite novel properties than the ordinary dusty plasma. The presence of negative ions in an ordinary dusty plasma has a considerable effect on the evolution of dust surface potential and dust charging process [24], and consequently it affects the wave phenomenon and sheath formation in the vicinity of material surface [25,26]. Therefore, the understanding of electronegative dusty plasma is important in various fields such as industrial plasma processing and space environments [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%